2021
DOI: 10.3390/jcs5040102
|View full text |Cite
|
Sign up to set email alerts
|

Isosteric Enthalpy Behavior of CO2 Adsorption on Micro-Mesoporous Materials: Carbon Microfibers (CMFs), SBA-15, and Amine-Functionalized SBA-15

Abstract: The isosteric enthalpy of adsorption (∆adsh ) of CO2 in three different micro and mesoporous materials was evaluated in this work. These materials were a microporous material with functional groups of nitrogen and oxygen (CMFs, carbon microfibers), a mesoporous material with silanol groups (SBA-15, Santa Barbara Amorphous), and a mesoporous material with amine groups (SBA-15_APTES, SBA-15 amine-functionalized with (3-Aminopropyl)-triethoxysilane). The temperature interval explored was between 263 K and 303 K, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…The most critical element of chemical adsorption of CO 2 involves the design and development of a suitable adsorbent, which consists of porous support onto which an amine is attached [7]. The adsorption of carbon dioxide has been studied in various mesoporous materials, including the MCM-41 and SBA-15 [8][9][10][11]. Different research groups have tried to introduce amine groups into mesoporous silicas because of their elevated surface area.…”
Section: Introductionmentioning
confidence: 99%
“…The most critical element of chemical adsorption of CO 2 involves the design and development of a suitable adsorbent, which consists of porous support onto which an amine is attached [7]. The adsorption of carbon dioxide has been studied in various mesoporous materials, including the MCM-41 and SBA-15 [8][9][10][11]. Different research groups have tried to introduce amine groups into mesoporous silicas because of their elevated surface area.…”
Section: Introductionmentioning
confidence: 99%
“…S9 and Table S5 †), and judging from the proles obtained and the values, it can easily be concluded that each of them shows chemisorption properties except APTES-GLU-Ex with lowest Q st exhibiting poor CO 2 interaction. 43,44 Based on the XPS analysis, it can be concluded that synthetic conditions have been optimized to tune the hybridization of nitrogen in these materials, which facilitates efficient uptake of CO 2 .…”
Section: Resultsmentioning
confidence: 99%
“…In this work, the isosteric enthalpy of adsorption has been calculated indirectly, that is, by using adsorption isotherms at different temperatures. It has been reported that when the process is dominated by physisorption, the temperatures selected for the analysis do not have much influence if the difference between them is not larger than 20 °C [ 43 ]. Five temperatures have been considered (−10, 0, 10, 20, and 30 °C).…”
Section: Resultsmentioning
confidence: 99%